Penerapan Nilai - Nilai Kebudayaan Terhadap Partisipasi Umat Dalam Perayaan Ekaristi Di Paroki Santa Maria Immaculata Wayun Palu- Rejo - Pebi Anggreini; Silvester Adinuhgra; Agnes Angi Dian Winei (Sepakat : Jurnal Pastoral Kateketik, 2023)
This research examines the application of cultural values towards the participation of the congregation in the Eucharistic celebration at the Parish of Santa Maria Immaculata Wayun Palu-Rejo, located in the district of South Barito, Central Kalimantan. The parish exemplifies unity and tolerance among the faithful from diverse ethnic and cultural backgrounds who participate in the Eucharistic celebration and other pastoral activities. A qualitative research method was employed, gathering data through interviews with 8 members of the congregation and 3 parish officials. The data were analyzed using Miles and Huberman's analysis method. The results of the study indicate that the congregation of the Parish of Santa Maria Immaculata Wayun Palu-Rejo has applied cultural values in their participation during the Eucharistic celebrations. The use of language, music, dance, and traditional attire is evident in the Inculturation Mass and other Eucharistic celebrations. The spirit of mutual cooperation, empathy, and care for fellow believers also influences the congregation's participation in the Eucharistic celebration. Pastoral efforts and catechesis conducted by the priests and parish officials play a vital role in encouraging the congregation to appreciate and apply cultural values in church activities. The priests convey messages and advice on the importance of cultural values during sermons and socialization. The Inculturation Mass serves as one of the initiatives to incorporate cultural values into the Eucharistic celebration. In conclusion, the application of cultural values significantly affects the participation of the congregation in the Eucharistic celebration at the Parish of Santa Maria Immaculata Wayun Palu-Rejo. Pastoral efforts and catechesis by the priests and church officials help raise awareness among the congregation regarding the significance of culture in religious life. Culture and congregation participation in the Eucharistic celebration are interconnected and require cooperation between church officials and the congregation. A suggestion for further research is to gain a deeper understanding and analyze the impact of cultural values on the participation of the congregation in other aspects of church life. Additionally, involving other ethnic groups in the study would provide a more comprehensive overview of the cultural diversity in this parish.